The pandemic divide : how COVID increased inequality in America - Wright, Gwendolyn L., 1962-; Hubbard, Lucas (Freelance writer); Darity, William A., Jr., 1953- (Duke University Press, 2022)
"As COVID-19 made inroads in the United States in spring 2020, a common refrain rose above the din: "We're all in this together." However, the full picture was far more complicated-and far less equitable. Black and Latinx populations suffered illnesses, outbreaks, and deaths at a much higher rate than the general populace. Those working in low paid jobs and those living in confined housing or communities already disproportionately beset by health problems were particularly vulnerable. The contributors to The Pandemic Divide explain how these and other racial disparities came to the forefront in 2020. They explore COVID-19's impact on multiple arenas of daily life-including wealth, health, housing, employment, and education-while highlighting what steps could have been taken to mitigate the full force of the pandemic. Most crucially, the contributors offer concrete public policy solutions that would allow the nation to effectively respond to future crises and improve the long-term well-being for all Americans. Contributors. Fenaba Addo, Steve Amendum, Leslie Babinski, Sandra Barnes, Mary T. Bassett, Keisha Bentley-Edwards, Kisha Daniels, William A. Darity Jr., Melania DiPietro, Jane Dokko, Fiona Greig, Adam Hollowell, Lucas Hubbard, Damon Jones, Steve Knotek, Arvind Krishnamurthy, Henry McKoy, N. Joyce Payne, Erica Phillips, Eugene Richardson, Paul Robbins, Jung Sakong, Marta Sánchez, Melissa Scott, Kristen Stephens, Joe Trotter, Chris Wheat, Gwendolyn L. Wright"--